Digital Communication Strategies of Homeless Accounts in Building Engagement on Instagram Platform - Revalina Amalia Mahdi; Hari Otang Sasmita (Communica : Journal of Communication, 2026)
This study investigates the digital communication strategies employed by “homeless accounts” non-formal, anonymously managed Instagram entities to build substantial engagement. Addressing the lack of scholarly attention to non-institutional media actors in Indonesia, this research examines how these accounts construct content typologies and apply strategic communication methods through a qualitative design combining non-participant digital observation and content analysis of 556 purposively selected accounts. The findings indicate that homeless accounts rely on viral-prone themes, emotional storytelling, and highly adaptive use of platform features such as reels, stories, and interactive stickers to maximize reach and resonance. These strategies collectively shape a communication pattern characterized by authenticity, algorithmic awareness, and dialogue-driven audience interaction, enabling these accounts to cultivate what may be termed a digital empathy community. The results further show that engagement is strengthened through a three-stage cycle consisting of trend-based pre-production, authenticity-centered production, and feedback-oriented post-production. This study concludes that homeless accounts demonstrate how digital influence can be generated outside traditional media structures through emotional resonance, participatory interaction, and platform-specific optimization. At the same time, concerns related to accountability and misinformation highlight the need for improved digital literacy and platform-level safeguards to support responsible communication.